Transición de la prensa tradicional al ecosistema digital Caso: El Comercio - Vicente Vicente, Noemí Lilia (2023)
Technology is present throughout our environment, even more so in the media, it is used by newspapers to perform the mediamorphosis and stay current. In this case, the causes and the transition process of the Ecuadorian newspaper El Comercio to the digital ecosystem were investigated, evaluating the importance of the new narratives in the transmission of information in this medium. For this research, the qualitative design was improved with the in-depth interview instrument to obtain the information that allowed determining the results in terms of migration, process and digital audiences. Finally, it was concluded that the new narratives, the skills of professionals in the management of equipment and technological tools are present in the construction and distribution of information for the new digital audiences.